Enhancing Person-Centered Audiologic Rehabilitation: Exploring the Use of an Interview Tool Based on the International Classification of Functioning, Disability, and Health Core Sets for Hearing Loss - Granberg, Sarah; Skagerstrand, Åsa (Frontiers in Rehabilitation Sciences, 2022)
Health care interventions that are intended to improve hearing should be based on the results of individual patient assessments. To improve these assessments, the feasibility of an International Classification of Functioning, Disability, and Health (ICF)-based interview tool was tested in a single clinical setting in Sweden. Audiologists participating in the study used the interview tool during a four-week testing period and provided written reflections after each session. The use of this tool was also evaluated in a focus group interview that took place after the completion of the project. The results of this study identified both process-related and structure-related factors that were highly relevant to the implementation of this interview tool. Overall, the findings revealed that the use of this interview tool promoted person-centered care in encounters focused on clinical audiological rehabilitation. Specifically, the ICF-based holistic approach permitted the audiologists to acquire more comprehensive patient narratives. The use of the ICF interview tool facilitated patient participation and permitted the audiologist to collect more substantial and meaningful information from each patient.